Digital Mindset In Civil Case Settlement Through Electronic Court (E-Court) In The Era Of Digital Transformation - Christy, Maria Acynta (IHSA Institute, 2023)
This study examines the importance of a digital mindset in responding to the challenges of digital transformation in resolving civil cases through E-Court. This study uses normative legal research methods. The results show that law enforcement officers must have digital knowledge, skills, and attitudes to answer the challenges of digital transformation in law enforcement, especially in handling civil cases through E-court. In contrast, the Supreme Court, as the State Judiciary Institution of the Republic of Indonesia, and the Organization of Advocates, as a Professional Organization authorized by law to carry out law enforcement functions, must have a structure, process, climate, or culture that supports digital transformation, as well as the perception that digital technology is a pillar of the organization's strategy. Organizational leaders need to have the characteristics of a digital mindset: have a high curiosity about digital technology, are up-to-date with new technologies, can utilize and use digital technology in every activity, and are willing to accept the challenges presented by digital technology